Vesical Teratoma: A Rare Case Presentation - Thapa, Narayan; Thapa, Bikash Bikram; Bhandari, Bharat Bahadur; Hamal, Bhairab Kumar (Medical Journal of Shree Birendra Hospital, 2017)
Dermoid cysts are extremely rare in the urinary bladder and pose a diagnostic dilemma to both the Urologist and the Histopathologist. Only a few cases were found documented and published in literature. We present a case of dermoid cyst in the urinary bladder presenting as a bladder mass which is very rare tumour. Diagnosis of this case was made cystoscopically and confirmed by histopathologically. Complete excision of mass was possible by endoscopic resection.